Perlunya Pemberian Pelayanan Lalu Lintas Penerbangan Aerodrome Control Service Combine di Bandar Udara Banyuwangi - Sirait, Eva Monica Edana; Putriekapuja, Rany Adiliawijaya (Politeknik Penerbangan Indonesia Curug, 2023)
I Gusti Ngurah Rai Airport is one of the busiest airports in Indonesia, serving approximately 430 traffic per day. Apart from providing services for flights to and from Bali, it also provides flight services to and from Lombok and Banyuwangi. This of course adds to the workload of ATC Bali, especially during peak hours. On the other hand, usually flights arriving from the east are served by TMA East and flights arriving from the west are served by TMA West, currently all flights are only served by TMA West. So during peak hours there was often an increase in the load of communication, which had caused a breakdown of separation and breakdown of coordination, involving VFR aircraft and IFR aircraft in the jurisdiction of Bali APP/TMA. This research was conducted with the aim of minimizing the potential for breakdown of separation and breakdown of coordination due to an increase in ATC Bali's load of communication in line with the increasing amount of traffic. The method used is descriptive qualitative. From this study it was found that breakdown of separation and breakdown of coordination can occur due to increased workload and load of communication of an ATC. Therefore, it is necessary to review the provision of air traffic services at the Denpasar Branch of Perum LPPNPI and at the Banyuwangi Sub-Branch Office.